Influencing factors of cardiorespiratory fitness in allogeneic stem cell transplant candidates prior to transplantation - Limbach, Matthias; Kühl, Rea; Dreger, Peter; Luft, Thomas; Rosenberger, Friederike; Kleindienst, Nikolaus; Friedmann-Bette, Birgit; Bondong, Andrea; Bohus, Martin; Wiskemann, Joachim (Supportive care in cancer, 2021)
Cardiorespiratory fitness (CRF) seems to be prognostic prior to allogeneic stem cell transplantation (allo-HSCT). Influencing factors of CRF in allo-HSCT candidates have not been studied so far. Aim was to identify potentially influencing factors on CRF.